PROGRAM GEMERLANG SEBAGAI STRATEGI MENINGKATKAN MINAT BACA SISWA DI SMP TARUNA ISLAM AL KAUTSAR - Ananta, Dewi; Susetya, Hemas Haryas Harja (Yayasan Amanah Nur Aman, 2025)
This study aims to describe the Gemerlang Program and its impact on students' reading interest at SMP Taruna Islam Al-Kautsar. This study uses a qualitative descriptive approach. The research sources are teachers and students at SMP Taruna Islam Al-Kautsar. The research data are from the principal and 10 eighth-grade students who took the literacy test. Data collection techniques were obtained through interviews. The results of the study indicate that the Gemerlang Program, which requires students to read non-fiction books, summarize them, and give presentations to demonstrate their potential for success in increasing students' reading interest, is effective. This program also combines the 3P approach (must read, must write, and must present), which further strengthens students' literacy, communication, and critical thinking skills. Overall, the Gemerlang Program is a strategic step that can be used as a model by other schools in their efforts to foster students' interest in reading. Based on previous research, most literacy programs in schools are still limited to independent reading activities or mere visits to the library without any structured follow-up to develop critical thinking, writing, and speaking skills in an integrated manner. Additionally, studies specifically evaluating the effectiveness of 3P-based literacy programs (guaranteed reading, guaranteed writing, and guaranteed presentation) systematically at the junior high school level are still very limited. Therefore, this research was conducted to address this gap through the implementation of the Gemerlang Program at SMP Taruna Islam Al-Kautsar.